Desenvolvimento de método quantitativo e estudo de geoquímica isotópica para monitorar a integridade das pastas de cimento de poços expostos a ambientes ricos em CO2 - Santos, Victor Hugo Jacks Mendes dos (2022)
Monitoring methods are essential for obtaining relevant information for companies to make decisions. In this context, it was proposed to study solutions to monitor the integrity of cement pastes from wells exposed to CO2-rich environments. In the quantitative method development study, partial least squares (PLS) regression models were calibrated and validated, quantifying, based on Fourier-transform infrared spectroscopy (FTIR) data, the CaCO3 content in cement pastes that underwent the carbonation process. In the isotopic geochemistry study, it was identified that the pH of the reaction medium and the solubility and pH of the mineral phases of cementitious materials are the main parameters that influence the kinetic and thermodynamic factors and the balance/distribution of carbon isotopes (13C and 12C) throughout the reaction system, and it was observed the potential of the stable isotope methods to discriminate the origin of CO2. Thus, in the present doctoral thesis: (i) rapid and reliable solutions were developed to monitor the CaCO3 content in carbonated cement pastes by FTIR and (ii) it was confirmed the potential of stable carbon isotopes (δ 13C) data to differentiate the origin of CO2 that induced the degradation process of the well cement pastes. From the results, it can be concluded that consistent data were obtained that led to the proposition of new alternatives to study and monitor the integrity of cement pastes from wells exposed to CO2-rich environments. In this way, the present work could contribute to the development of the area of engineering and technology of cementitious materials for application in oil and gas (O&G) wells and in the Carbon Capture and Storage (CCS) context.